Africa and Its People in the Polish Media - Średziński, Paweł (Werkwinkel, 2017)
The African continent is treated by the Polish media marginally and usually seen through the lens of four domains of stereotypical perceptions that are associated with difficult life conditions, threats and dangers, beautiful and wild nature, as well as original and diverse cultures. Monitoring of the Polish media has become very important in this situation. That is why the results of first media monitoring report were published in 2011 by ‘Africa Another Way’ Foundation. Five years later the monitoring was repeated. It is hard to resist the impression that Africa is still viewed as this poor, underdeveloped and dangerous continent. And the way it is presented translates into the way individuals of African descent are perceived.